Resilience of hospital staff facing COVID-19 pandemic: Lessons from Israel - Trotzky, Daniel; Aizik, Uri; Mosery, Jonathan; Carady, Natali; Tavori, Guy; Cohen, Aya; Pachys, Gal; Avraham, Miri; Levtzion-Korach, Osnat; Tal, Orna (Frontiers in Public Health, 2023)
Introduction The COVID-19 pandemic has placed additional burden on already strained healthcare systems worldwide, intensifying the responsibility and burden of healthcare workers. Although most hospital staff continued working during this stressful and challenging unprecedented pandemic, differences in the characteristics and attributes were noted between sectors and hospital departments. Israeli healthcare workers are trained and experienced in coping with national emergencies, but the pandemic has exposed variations in staff reactions. Understanding the intrinsic differences between sectors and departments is a key factor in staff and hospital preparedness for unexpected events, better resource utilization for timely interventions to mitigate risk and improve staff wellbeing. Objective To identify and compare the level of resilience, secondary traumatization and burnout among hospital workers, between different sectors and hospital departments, during the COVID-19 pandemic. Methods Cross-sectional research to assess the resiliency, secondary traumatization and burnout of healthcare workers at a large general public hospital in central Israel. The sample consisted of 655 participants across various hospital units exposed to COVID-19 patients. Results Emergency department physicians had higher rates of resilience and lower rates of burnout and secondary traumatization than staff in other hospital departments. In contrast, staff from internal medicine departments demonstrated the highest levels of burnout (4.29). Overall, physicians demonstrated higher levels of resilience (7.26) and lower levels of burnout compared to other workers. Conclusion Identifying resilience characteristics across hospital staff, sectors and departments can guide hospital management in education, preparation and training of healthcare workers for future large-scale health emergencies such as pandemics, natural disasters, and war.